Social Democracy in the Making: Political and Religious Roots of European Socialism - Dorrien, Gary J. (Yale University Press, 2019)
Cover -- Half Title -- Title -- Copyright -- Dedication -- Contents -- Preface -- CHAPTER ONE: Christian Socialism in the Making of Social Democracy -- CHAPTER TWO: British Origins: Anglican Socialism, Early Marxism, and Fabian Collectivism -- CHAPTER THREE: German Social Democracy: Marxism as Theory and Politics -- CHAPTER FOUR: Germanic Political Theology: Social Democracy as Theology -- CHAPTER FIVE: British Breakthrough: Guild Socialist Visions and Social Democratic Realities -- CHAPTER SIX: Democratic Socialism as Pluralistic Social Democracy -- Notes -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- X -- Y -- Z.